PENGARUH SISTEM INFORMASI SUMBER DAYA MANUSIA, DIGITALISASI PELATIHAN, DAN KOMITMEN TERHADAP KINERJA DOSEN DENGAN DUKUNGAN TEKNOLOGI SEBAGAI VARIABEL MEDIASI (STUDI PADA PERGURUAN TINGGI TANGERANG) - Rinintha Parameswari; Nana Sutisna; Agus Kusnawan (LPPM Universitas Buddhi Dharma, 2026)
This study aims to analyze the effects of Human Resource Information Systems (HRIS), training digitalization, and commitment on lecturer performance, with technology support as a mediating variable. The study was conducted on lecturers at higher education institutions in the Tangerang area using a quantitative survey approach. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that training digitalization has a positive and significant effect on technology support. Meanwhile, Human Resource Information Systems and Commitment do not show a significant effect on technology support. Regarding lecturer performance, training digitalization has a significant effect with a negative direction, while commitment has a positive and significant effect. Human Resource Information Systems and Technology support do not show a significant effect on lecturer performance. In addition, technology support is not proven to mediate the effects of Human Resource Information Systems, training digitalization, and commitment on lecturer performance. These findings suggest that lecturer performance is more strongly influenced by individual factors and the effectiveness of training than by information systems and technology support directly. This study reinforces the relevance of the Theory of Planned Behavior in explaining lecturer performance behavior within the context of digital transformation in higher education.